Nitrogen-fixing bacteria and organic ameliorant for corn growth and yield increment in Inceptisols - Reginawanti Hindersah; Nadia Nuraniya Kamaluddin; Shabrina Rahma Fauzia; Mieke Rochimi Setiawati; Tualar Simarmata (Journal of Degraded and Mining Lands Management, 2022)
Since Inceptisols, in general, contain low soil organic matter and major plant nutrients, inorganic fertilizers are commonly added during corn cultivation. In order to maintain long-term soil health and fertility, bioferilizer and organic ameliorant application are suggested. The addition of nitrogen (N)-fixing bacteria (NFB) can benefit plant growth through the supply of available nitrogen for plant uptake. Organic ameliorants can enhance soil chemical and biological properties. A field trial had been performed to observe the effect of biofertilizer and organic ameliorant on corn growth, N status in soil and plant, and the yield and wasteof corn. The experiment was designed in a Completely Randomized Block Design that consisted of four treatments and six replications. The treatments were 1.2 kg/ha N-fixing mixed biofertilizer, 2 t/ha organic ameliorant, and mixtures of biofertilizer and ameliorant. Control plants received neither biofertilizer nor ameliorant. The experiment results found that N-fixing biofertilizer and ameliorant increased plant height, fully-developed leaves number, soil reaction and N uptake of corn compared to the control. The total-N content was slightly increased after NFB inoculation with and without amelioration over other treatments. Plots treated with biofertilizer and ameliorant produced a higher grain weight compared to the control treatment. Corn wastes such as empty corn cob and husk weight were increased in plants treated with biofertilizer, ameliorant and a combination of both. This study suggested that the combined application of biofertilizer and ameliorant produced 66% more grain yield and 84 % more cob and husk waste compared to untreated plants.